A pilot study on spatial hearing in children with congenital unilateral aural atresia - Josefsson Dahlgren, Hanna; Engmér Berglin, Cecilia; Hultcrantz, Malou; Asp, Filip (Frontiers in Pediatrics, 2023)
Congenital aural atresia is a malformation of the external ear canal that affect approximately 2.4 of 10 000 children born in Sweden. Today, children are offered bone conduction hearing devices to restore hearing in the affected ear from infancy regardless of whether the malformation is unilateral or bilateral. The benefit from unilateral amplification varies between individuals for reasons not entirely understood. There is also little knowledge on how early fitting with a BCD will affect the development of spatial hearing. This paper has sought to study the effect on spatial hearing from fitting before three years of age with a bone conduction device in individuals with unilateral aural atresia, using set-ups that are similar to situations in daily life. A possible connection between unaided sound localization accuracy and unaided hearing thresholds in the atretic ear was found, a correlation that has not previously been found in children. The results show that the individuals that present the worst unaided sound localization accuracy have the most benefit from amplification, and that sound localization accuracy might be predictive of the degree of benefit from amplification. These results might provide clinicians with important information when counselling individuals with unilateral aural atresia.